Modeling Emergency Supply Flexibility in a Two-Echelon Inventory System - Alfredsson, Patrik; Verrijdt, Jos (Management Science, 1999)
We consider a two-echelon inventory system for service parts. To obtain high service levels at a low cost we allow not only for normal supply of parts but also for emergency supply options in terms of lateral transshipments and direct deliveries. After presenting the strategy we use for satisfying customer demand, we construct an analytical model that we use to calculate relevant performance measures. Simulation shows that our model produces accurate estimates, and that the performance of the inventory system is insensitive to the lead-time distribution. After introducing a cost structure we show that the strategy we propose can result in considerable savings when compared to using only normal supply. Comparison of the results of our model with the results of other models indicates that the combined use of lateral transshipments and direct deliveries can lead to significant cost savings.